The VARIATIONS IN THE ADDITION OF SNAKEHEAD FISH (Channa striata) FLOUR ON THE LEVEL OF FAVORABILITY AND NUTRITIONAL PROFILE OF VELVET BEAN TEMPEH - Syauqibik, Achmad; Junianto, Junianto; Fitrianto, Nur; Rostini, Iis (Jurnal Perikanan Unram, 2025)
This research utilizes the potential of snakehead fish (Channa striata) rich in albumin (62.9%) and essential nutrients for functional food development. Snakehead fish has superior nutritional value with 25.2% protein, important minerals such as calcium and phosphorus, and essential amino acids that play roles in growth and immune system. The effort to diversify snakehead fish processing into flour and its fortification into velvet bean (Mucuna pruriens) tempeh was carried out to increase nutritional value and consumer acceptance. The research employed an experimental method with 4 treatments of snakehead fish meat flour addition: 0% (TB0), 8.5% (TB1), 9.5% (TB2), and 10.5% (TB3). Parameters tested included organoleptic properties and proximate analysis. Results showed formula TB2 (9.5%) obtained the highest alternative value (6.58) with 39.34% protein content, 13.89% fat, 8.90% moisture, 2.43% ash, and 43.10% carbohydrate. Compared to control, the addition of snakehead fish flour increased protein content by 8.49% and decreased fat content by 5.39%. It can be concluded that the fortification of 9.5% snakehead fish flour produced velvet bean tempeh with the highest organoleptic acceptance and successfully utilized local food ingredients to produce highly nutritious functional food acceptable to consumers.